Avaliação da via da adenosina deaminase/CD26 na proliferação celular e na progressão do câncer de esôfago - Silveira, Laisa Helena Silva (2022)
Esophageal cancer is among the most diagnosed cancer worldwide and the sixth most common cause of cancer-related death. During tumor growth, ATP (adenosine triphosphate) and its metabolites are actively secreted into the extracellular environment, where they act as extracellular messengers. Accumulated adenosine can be degraded to inosine in the presence of adenosine deaminase (ADA) through association with CD26. The role of adenosine in tumor escape has been intensively studied. Therefore, the aim of this study was to evaluate the adenosine deaminase/CD26 pathway in the esophageal cancer progression. To evaluate this pathway in cell proliferation of esophageal cancer, three cell lines of esophageal cancer were used, two representing squamous cell carcinoma (ESCC) and the other representing adenocarcinoma (EAC). We evaluated the cell viability, qRT-PCR, and nucleotide enzymatic activity. In addition, we performed a retrospective cohort patient data analysis and performed immunohistochemistry analysis for CD26. We also evaluated in the Tumor Cancer genome Atlas (TCGA) the relation of CD26 expression and patient overall survival. Our results from TCGA showed that the high expression of CD26 is correlated with a higher survival rate, and the CD26 expression was higher in patients with adenocarcinoma. Regarding the experiments of cell viability and cell count, adenosine promoted a significant reduction in cell proliferation at 1 and 5 mM after 24 and 48 h of treatment for OE21 and OE33 cell lines. Inosine promoted a significant reduction in cell proliferation at the concentration of 5 mM in the Kyse-450 cell line. Experiments with qRT-PCR showed no significant difference for both CD26 and ADA expression in esophageal cell lines treated with inosine. Furthermore, the hydrolysis profile of adenine nucleotides showed that ESCC cells preferentially hydrolyze AMP. Interestingly, the adenocarcinoma cells showed a high hydrolysis profile of the three nucleotides with significantly different levels. Thus, our results demonstrate the involvement of the ADA/CD26 pathway in cell proliferation and progression of esophageal cancer.